2015
DOI: 10.1080/09168451.2015.1061417
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of microRNA214 and transcriptional regulation in reductions in mevalonate pyrophosphate decarboxylase mRNA levels in stroke-prone spontaneously hypertensive rat livers

Abstract: Hypocholesterolemia has been epidemiologically identified as one of the causes of stroke (cerebral hemorrhage). We previously reported that lower protein levels of mevalonate pyrophosphate decarboxylase (MPD), which is responsible for reducing serum cholesterol levels in stroke-prone spontaneously hypertensive rats (SHRSP), in the liver were caused by a reduction in mRNA levels. However, the mechanism responsible for reducing MPD expression levels in the SHRSP liver remains unclear. Thus, we compared microRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…22) Similar results (results of serum total cholesterol, HDL-, or VLDL/LDL-cholesterol) were obtained between WKY and SHRSP in the present study (data not shown). In order to identify the causes of these reductions in serum cholesterol and cholesterol content in the livers of SHRSP, the mRNA levels of LDLR, SRB1, and Abca1 were Fig.…”
Section: Comparison Of Ldlr Srb1 and Abca1 Mrna And Protein Levels supporting
confidence: 91%
See 2 more Smart Citations
“…22) Similar results (results of serum total cholesterol, HDL-, or VLDL/LDL-cholesterol) were obtained between WKY and SHRSP in the present study (data not shown). In order to identify the causes of these reductions in serum cholesterol and cholesterol content in the livers of SHRSP, the mRNA levels of LDLR, SRB1, and Abca1 were Fig.…”
Section: Comparison Of Ldlr Srb1 and Abca1 Mrna And Protein Levels supporting
confidence: 91%
“…21) Furthermore, we found that reductions in MPD expression levels in the livers of SHRSP were suggested to be controlled by the upregulation of microRNA (miR)-214 and downregulation of transcriptional levels. 22) miR was shown to reduce protein levels by inhibiting its synthesis from mRNA or accelerating the degradation of mRNA. 23,24) Recently, it was reported that phosphomevalonate kinase (PMVK), isopentenyl pyrophosphate isomerase (IPI), farnesyl pyrophosphate synthase (FPS), squalene synthase (SQS), squalene epoxidase (SQE), lanosterol synthase (LSS), methylsterol monooxygenase (Sc4mol) and hydroxysteroid (17β) dehydrogenase 7 (Hsd17b7) in the liver of SHRSP were significantly less than 50% those in WKY, when the mRNA levels of 22 cholesterol biosynthetic enzymes measured by real-time polymerase chain reaction (PCR).…”
Section: 2)mentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the hnRNA levels of HSD17B7 were significantly lower in SHRSP than in WKY, indicating that the reduced expression of HSD17B7 in SHRSP was indeed due to transcriptional regulation (Figure ). We had previously reported that the low levels of MPD were also caused by a decrease in transcription . Although sterol regulatory element‐binding proteins (SREBP) are well known transcriptional factors that inhibit cholesterol biosynthetic enzymes such as MPD and HSD17B7, no significant differences were observed in SREBP‐2 levels in the liver of SHRSP and WKY.…”
Section: Discussionmentioning
confidence: 99%
“…We have also previously shown that relative mRNA levels of IPI, SQS, LSS, sterol‐C5‐desaturase (SC5D), and 7‐dehydrocholesterol reductase (DHCR7) in the liver of SHRSP were the same as those in WKY . Further, the relative mRNA and protein levels of MPD and SQE were lower in the liver of SHRSP than in WKY . Anderson et al reported a correlation coefficiency of 0.48 between the abundance of mRNA and protein as determined by transcriptome and proteome analysis, suggesting that post‐transcriptional regulation of gene expression is a frequent phenomenon in higher organisms.…”
Section: Introductionmentioning
confidence: 90%